Analisis faktor-faktor yang mempengaruhi keputusan pembelian produk Nobby Hijab Salatiga, dengan trust sebagai variabel pemoderasi - Anggraini, Destya Kusuma; Mochlasin, Mochlasin (Journal of Halal Industry Studies, 2023)
This research aims to determine the influence of lifestyle, product quality, and religiosity on purchasing decisions by using the trust variable as moderation. This type of research is quantitative and primary data is obtained through a questionnaire instrument. The research sample consisted of 96 consumers who had made purchases at Nobby Hijab Salatiga. Data were analyzed using statistical tests and MRA tests. Based on the research results, lifestyle and religiosity variables have a positive effect on purchasing decisions. Meanwhile, the product quality variable is proven to have no effect and is not significant on purchasing decisions. The majority of consumers do not make product quality their main goal. Consumers make purchases because they are obliged to fulfill basic needs. Based on the MRA test results, trust is able to moderate the influence of lifestyle, product quality and religiosity on purchasing decisions for Nobby Hijab Salatiga products.